Efektivitas Media Pembelajaran Nearpod Dalam Pembelajaran Personalpronomen Im Akkusativ Siswa SMA - Mochammad Iqbal Nizzhar, - (2023)
Personal pronouns play a significant role in mastering German grammar. To acquire a good understanding of pronoun forms, the use of instructional media that supports the learning process is essential. In modern era, educational applications have become a popular choice due to the widespread use of smartphones, one of which is NearPod. The aim of this study is to determine: 1) The proficiency of students in mastering the topic of Personalpronomen im Akkusativ prior to using NearPod, 2) The proficiency of students in mastering the topic of Personalpronomen im Akkusativ after using NearPod, 3) The effectiveness of NearPod in enhancing students' learning abilities in the topic of Personalpronomen im Akkusativ, 4) Students' responses to NearPod as an instructional medium. The research methodology employed is quantitative with a Quasi Experiment design. The population of this study consists of all tenth-grade students in the even semester of the 2022/2023 academic year at SMA Negeri 4 Cimahi, with a sample size of 30 students from class X IPA 2 as the experimental group and 30 students from class X IPA 3 as the control group. The findings of this study are as follows: 1) The initial proficiency of students in the experimental group is categorized as "below average," while the control group is classified as "failed," 2) After using NearPod, the proficiency of students in the experimental group is classified as "good," whereas the control group is categorized as "sufficient", 3) Based on the results of the Independent Sample t-Test, the use of NearPod as an instructional medium for Personalpronomen im Akkusativ is proven to be effective. This is evidenced by the significance value (2-Tailed) being less than 0.05 (0.00 < 0.05). In other words, there is a significant influence between learning using NearPod and conventional learning in the mastery of Personalpronomen im Akkusativ. 4) The majority of students agree with the use of NearPod in learning Personalpronomen im Akkusativ.